A Bis‐(carbone) Pincer Ligand and Its Coordinative Behavior toward Multi‐Metallic Configurations. (30th March 2022) - Aweke, Bamlaku Semagne; Yu, Cheng‐Han; Zhi, Minna; Chen, Wen‐Ching; Yap, Glenn P. A.; Zhao, Lili; Ong, Tiow‐Gan
Abstract: Carbones are divalent carbon(0) species that contain two lone pairs of electrons. Herein, we have prepared the first known stable and isolable free bis ‐(carbone) pincer framework with a well‐defined solid‐state structure. This bis ‐(carbone) ligand is an effective scaffold for forming monometallic (Ni and Pd) and trinuclear heterometallic complexes with Au−Pd−Au, Au−Ni−Au, and Cu−Ni−Cu configurations. Sophisticated quantum‐theoretical analyses found that the metal–metal interactions are too weak to play a significant role in upholding these multi‐metallic configurations; rather, the four lone pairs of electrons within the bis ‐(carbone) framework are the main contributors to the stability of the complexes. Abstract : A stable bis‐ (carbone) pincer ligand was prepared and its structural characterization reported. With a total of five electron pairs available, this new pincer framework was studied for its coordinative behavior, enabling the formation of trinuclear heterometallic complexes.